2018
DOI: 10.2214/ajr.17.18516
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Clinically Significant Prostate Cancer Associated With Prostate Imaging Reporting and Data System Category 3 (Equivocal) Lesions Identified on Multiparametric Prostate MRI

Abstract: Incorporating clinical parameters into risk stratification algorithms may improve the ability to detect clinically significant disease among PI-RADS category 3 lesions and may aid in the decision to perform biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 20 publications
8
34
0
Order By: Relevance
“…Diverse diagnostic and monitoring strategies have been investigated previously; these have involved adding clinical parameters or subcharacteristics of target lesions to mpMRI results. [17][18][19][20] We here confirmed the value of PSAD as a csPCa predictor in PI-RADS 3 patients. Washino et al showed that the PI-RADS version 2 score and PSAD were independent risk factors for PCa and csPCa.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Diverse diagnostic and monitoring strategies have been investigated previously; these have involved adding clinical parameters or subcharacteristics of target lesions to mpMRI results. [17][18][19][20] We here confirmed the value of PSAD as a csPCa predictor in PI-RADS 3 patients. Washino et al showed that the PI-RADS version 2 score and PSAD were independent risk factors for PCa and csPCa.…”
Section: Discussionsupporting
confidence: 82%
“…Diverse diagnostic and monitoring strategies have been investigated previously; these have involved adding clinical parameters or subcharacteristics of target lesions to mpMRI results . We here confirmed the value of PSAD as a csPCa predictor in PI‐RADS 3 patients.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the overall and clinically significant CDR in all the patients with PI‐RADS 3 lesions was 25.3% and 22.2%, respectively. In contrast, the overall and significant CDR in the study by Sheridan et al was 27% and 17.1%, respectively 13 . They used a combined biopsy method (targeted + standard) in their study.…”
Section: Discussionmentioning
confidence: 81%
“…Based on these findings, we suggest using those parameters which are useful for characterization of PI‐RADS 3 lesions for making more accurate decisions. The only study employing clinical parameters for the evaluation of PI‐RADS 3 lesions was conducted by Sheridan et al in 2017, who evaluated a total of 111 PI‐RADS 3 lesions and defined several risk factors for PCa, such as age, prostate volume, and abnormal DRE 13 . Based on the total number of these risk factors, the authors revealed that the CDR ranged between 4% and 67%.…”
Section: Discussionmentioning
confidence: 99%
“…Sathianathen, et al15 argued that repeat biopsy of PI-RADS 3 lesions could be avoided in men who have undergone a negative TRUS biopsy because of the low rate of prostate cancer detection. Sheridan, et al16 also reported a lower detection rate for PI-RADS 3 lesions. They reported that, of 111 PI-RADS category 3 lesions, 81 (73.0%) were benign, 11 (9.9%) were not clinically significant, and 19 (17.1%) were clinically significant.…”
Section: Discussionmentioning
confidence: 96%